High-altitude shorebird migration in the absence of topographical barriers: avoiding high air temperatures and searching for profitable winds. Issue 1881 (27th June 2018) - Senner, Nathan R.; Stager, Maria; Verhoeven, Mo A.; Cheviron, Zachary A.; Piersma, Theunis; Bouten, Willem
Abstract : Nearly 20% of all bird species migrate between breeding and nonbreeding sites annually. Their migrations include storied feats of endurance and physiology, from non-stop trans-Pacific crossings to flights at the cruising altitudes of jetliners. Despite intense interest in these performances, there remains great uncertainty about which factors most directly influence bird behaviour during migratory flights. We used GPS trackers that measure an individual's altitude and wingbeat frequency to track the migration of black-tailed godwits ( Limosa limosa ) and identify the abiotic factors influencing their in-flight migratory behaviour. We found that godwits flew at altitudes above 5000 m during 21% of all migratory flights, and reached maximum flight altitudes of nearly 6000 m. The partial pressure of oxygen at these altitudes is less than 50% of that at sea level, yet these extremely high flights occurred in the absence of topographical barriers. Instead, they were associated with high air temperatures at lower altitudes and increasing wind support at higher altitudes. Our results therefore suggest that wind, temperature and topography all play a role in determining migratory behaviour, but that their relative importance is context dependent. Extremely high-altitude flights may thus not be especially rare, but they may only occur in very specific environmental contexts.